آليات حماية البيئة في الشريعة الإسلامية والتشريع الجزائري - خنوفة, حياة (University of Eloued جامعة الوادي, 2020)
"الملخص يستهدف البحث موضوع البيئة وهي عبارة عن الوسط الذي تعيش فيه جميع الكائنات الحية، ولقد اهتم بها كل من الشريعة الإسلامية والتشريع الجزائري في مجموعة النصوص الشرعية والقانونية من أجل الحفاظ على حياة هذه الكائنات، ولقد جاءت هذه الدراسة معنونه بــ: آليات حماية البيئة في الشريعة الإسلامية والتشريع الجزائري. وقد انطلقت من إشكالية تمثلت في: إلى أي مدى توافق التشريع الجزائري مع الشريعة الإسلامية في اتخاذ الإجراءات اللازمة لحماية البيئة؟ للإجابة عن هذا الإشكال قسمنا بحثنا إلى مبحث تمهيدي تناولنا فيه الإطار المفاهيمي لحدود الدراسة والمبحث الأول تناولنا فيه الآليات الوقائية لحماية البيئة في الشريعة الإسلامية والتشريع الجزائري, والمبحث الثاني تناولنا فيه الآليات الردعية لحماية البيئة في الشريعة الإسلامية والتشريع الجزائري، وتوصلنا إلى أنه" tهوالقانون الجزائري في وضع آليات حماية البيئة كان قائما فقط على مستوى الاصطلاح وإلا فالإجراءات التطبيقية هي ذاتها."الاسلاميةناك توافق بين التشريع ا الجزائري والشريعة الإسلامية في وضع آليات حماية البيئة، ولاحظنا من خلال الدراسة أن الاختلاف بين الشريعة abstrac The research aims at the subject of the environment, which is the medium in which all living organisms live. It has been included in both Islamic law and Algerian legislation in the form of legal and legal texts. Islamic law and Algerian legislation, and based on the problematic in this matter, which is: To what extent is the Algerian legislation compatible with Islamic Sharia in taking the necessary measures to protect the environment?And to answer on this issue,we divided our research into an introductory topic in which we discussed the conceptual framework for the limits of the study and the first topic in which we discussed the preventive mechanisms for environmental protection in Islamic law and Algerian legislation, and the second topic in which we discussed the deterrent mechanisms for environmental protection in Islamic law and Algerian legislation, and we concluded that there is a compatibility between Islamic law And Algerian legislation in the development of mechanisms to protect the environment, and we noticed through the study that there was a difference between Islamic law and Algerian law in the development of mechanisms to protect the environment, which is in the naming of terms. "
مذكرة ماستر تخصص شريعة وقانون
Keywords: البيئة/ الكائنات الحية/الآليات الردعية لحماية البئية/البيئة الجوية/البيئة المائية/البيئة البرية; The environment/Organisms/Deterrent mechanisms to protect the environment/The air environment/The air environment/Wild environment